Whole Blood Mitochondrial DNA Depletion in Human Immunodeficiency Virus-Infected Children - van der Watt, George Frederick (Division of Chemical Pathology, 2014)
Background: Nucleoside reverse transcriptase inhibitors (NRTIs) interfere with mitochondrial DNA polymerase gamma causing significant toxic effects, including fatal lactic acidosis. Little is known about mitochondrial DNA (mtDNA) in human immunodeficiency virus (HIV) infected children who face a lifetime exposure to these agents. We performed a cross sectional observation of mtDNA levels in whole blood in a pediatric population to ascertain the relationship between mtDNA, NRTI regimens and parameters of HIV-infection severity. Methods: Whole blood mt:nDNA ratios were determined by real-time PCR in three groups: 27 presumed HIV-negative, 89 HIV-infected, NRTI-treated and 62 HIV-infected treatment-naive children. Multivariate analysis was used to identify variables independently associated with mtDNA depletion. Results: Mean mt:nDNA ratios were lower (P < 0.001) at 77% of control in the HIVinfected antiretroviral treatment (ART) Naïve group and 73% of control in the ART group, but not different between the two HIV-infected groups. Mt:nDNA ratios were negatively associated with age (P = 0.029), HIV status (P < 0.0001) and Log10 of the HIV-1 viral load (P = 0.035) and positively associated with CD4 % (p = 0.032). A 6 stavudine vs zidovudine based regimen was associated with lower but not significant levels of mtDNA (P = 0.1). Conclusions: Depletion of whole blood mtDNA in children is associated independently with HIV-infection and markers of HIV infection severity, and does not improve with either stavudine or zidovudine based ART despite virological control, suggesting that these agents also deplete mtDNA.